Cherubism: early surgical approach and its effects on the quality of life in a pediatric patient - Cunha , Laryssa Thainá Mello Queiroz; Pereira, Almira Oliveira; Santos, Roniery Correia; Zancopé , Eduardo; Pinto, Sebastião Alves; Félix , Valtuir Barbosa; Silveira , Rubens Jorge (Journal of Oral Diagnosis, 2025)
Cherubism is a rare fibro-osseous osteodysplasia characterized by the symmetrical expansion of the jaws, often leading to facial deformities and functional impairment. This study presents the case of a pediatric patient diagnosed with cherubism who underwent early surgical intervention to improve quality of life and reduce the psychosocial impacts associated with the disease. The PedsQL™ 4.0 questionnaire was applied to assess quality of life before and after the surgical procedure. The results demonstrated a significant improvement in the social and school domains, reflecting a reduction in the psychosocial burden of cherubism. Six months post-procedure, no significant complications or signs of recurrence were observed, highlighting the efficacy of early intervention. These findings suggest that an early surgical approach is a valuable strategy for optimizing quality of life and minimizing the negative effects of cherubism, particularly in children undergoing social and academic development.